BARONG MEETING AT PUCAK PADANG DAWA TEMPLE BATURITI TABANAN REGENCY: IN THE PERSPECTIVE OF CULTURAL STUDIES - Dana, I Wayan; Dibia, I Wayan; Putra Agung, A.A. Gde; Suastika, I Made (E-Journal of Cultural Studies; Vol. 3, No. 2 Juli 2009)
This dissertation contains research findings on the Barong Meeting, a multidimentionalcultural event performed at Pucak Padang Dawa Temple, Baturiti Tabanan Regency. Such ameeting is attended by more than sixty various barongs and rangdas of various types comingfrom various areas in Central Bali, and is the biggest in Bali. The research on such a culturalphenomenon is intended to reveal holistically the existence of the Barong Meeting while theprocess of modernization is taking place in Bali nowadays.Such a cultural phenomenon was investigated based on the problems formulated inseveral research questions. (1) How is the Barong Meeting performed at Pucak Padang DawaTemple, Baturiti, Tabanan Regency?; (2) what ideology is referred to by the Barong Meeting atPucak Padang Dawa Temple, Baturiti, Tabanan Regency?; (3) What does the Barong Meetingmean viewed from the socio cultural system of the Balinese society?By applying qualitative method and regarding the Barong Meeting as a multilayerentity, this study is intended to understand and analyze the ideology and meaning contained inthe Barong Meeting, which is believed to have centralistic strength making the cultures fromvarious areas of Central Bali meet. The problems were solved by applying some relevanttheories such as the theory of power relationship, the theory of religions, the theory of esthetics,and the theory of semiotics.Five important findings of this study are; Firstly, the Barong Meeting at Pucak PadangDawa Temple is a cultural event with religious, social and theatrical dimensions. Secondly, theBarong Meeting is an old religious ritual viewed from what is stated in Purana of the LuhurPucak Padang Dawa Temple. Such a Barong Meeting is still carried out by the society membersat Bangli Village. Thirdly, the Barong Meeting is a cultural event covering the areas of CentralBali such as Tabanan Regency, Negara Regency, Badung Regency, Gianyar Regency and BangliRegency. Fourthly, the Barong Meeting is not an event which is habitually carried out but aritual ceremony which is dynamically repeated by absorbing innovations which still refer to thephilosophy and ethics of Hinduism, making it able to develop collective awareness respectingdiversity featuring the era’s life. Fifthly, the Barong Meeting is a religious event realizingconcrete, real and direct actions based on Hindusm. Such a ritual ceremony densely containingartistic values emphasizes the dynamic relationship and integratedness of performance of artsand art performance in the cultural activities performed in Bali Hindu. What can be concluded in this study shows that the Barong Meeting at Pucak PadangDawa Temple, Baturiti, Tabanan Regency, serves as an inviting and attending processioncovering the initial, the essence, and the end which is both centripetal and centrifugal. Theideology referred to is worshipping, power, and performance. The integration of these three basicideas present ritual ceremony dimension, social activity, and art performance, making the BarongMeeting a multidimensional event. The Barong Meeting contains multilayer senses such asmagic religious, socio unifier, politics of authority, economics and esthetics.
Keywords: Cultural event, Barong Meeting, Pucak Padang Dawa Temple